Statistical Model of Normal Contact Stiffness of Fixed Joint Surface during Unloading after First Loading - Donghua Yin; Xueliang Zhang; Yonghui Chen; Guosheng Lan; Yanhui Wang; Shuhua Wen (Advances in Materials Science and Engineering)
Based on Kogut and Etsion’s model (KE model), a statistical method is used to establish a model of normal contact stiffness of fixed joint surface during unloading after first loading. Simulation results show that, for the elastoplastic contact, normal contact stiffness of joint surface is the nonlinear function of mean surface separation during loading and unloading and decreases as the separation increases. For different plasticity indexes, the normal contact stiffness of joint surface varies differently following the change of mean surface separation during loading and unloading.